Reactor Solutions for Voltage Control of SWER Systems - Mayer, J.; Hosseinzadeh, N.; Wolfs, Peter (Victoria University, 2006)
Ergon Energy operates tens of thousands of kilometers of Single Wire Earth Return (SWER) distribution feeders in remote parts of Queensland to deliver electrical energy to small customer loads, scattered sparsely over vast areas. Ergon Energy has identified voltage regulation as one of the key issues being faced in this area, as loads continue to grow in rural distribution networks. These voltage regulation issues cause capacity limitations on the SWER feeders. Voltage drop during peak load periods is one issue, but high voltages during low load periods caused by the Ferranti effect is another key factor on long SWER feeders. Currently, Ergon uses fixed shunt reactors to control line overvoltages during low load periods, but these reactors add to the line load during peak load conditions. At AUPEC 2005, Central Queensland University presented a thyristor controlled reactor option as a potential solution to this problem. This paper follows on from this and presents two lower technology solutions, namely switched reactors and saturable reactors. Both options aim to reduce the steady state voltage range between peak load and low load, thus freeing up additional capacity on the SWER feeder for growing load. This paper presents the development of both options and comments on the suitability of the options to perform to the required specifications. PSCAD/EMTDCis used to model the problem.